Epidemiological profile of patients seen in the pre-anesthetic assessment clinic of a university hospital - Santos,Monica Loureiro (2017)
Abstract Objective Assess the demographic and clinical characteristics of surgical patients seen in the Pre-anesthetic Assessment Clinic of the Hospital Universitário Gaffrée e Guinle (APA/HUGG), in order to assist in the pursuit for quality, effectiveness, and resource rationalization of hospital management. Method Cross-sectional descriptive study with 491 patients undergoing elective surgery, treated at APA/HUGG Clinic from March to December 2014. The following variables were assessed: sex, age, BMI, smoking status, associated diseases, classification of MET's and ASA, presence of decompensated disease, medical associated appointments interconsultation, specialty and surgical risk, history of prior anesthetic-surgical procedure, and complications. Results There was a predominance of female (64.8%) and overweight patients (55.9%), aged 18-59 years. The prevalence of associated diseases was high (71.3%), with hypertension pressure prevailing (50.1%). Most patients had clinically compensated morbidity (96.3%) and long-term use of medication (77.4%). Regarding the surgical characteristics, the most frequent specialty was general and medium risk surgeries. The analysis of the characteristics by age showed that the elderly have more associated diseases and long-term use of medication, in addition to predominance of ASA II-III. Conclusion The epidemiological profile of surgical patients seen at the APA/HUGG was female, age 18-59 years, overweight, with associated diseases, long-term use of medication, without clinical decompensation, ASA II and MET's ≥4. Knowledge of the clinical characteristics of surgical patients is critical to schedule the perioperative care, allowing the improvement of quality and safety in anesthesia and surgery.